2010
DOI: 10.1088/0264-9381/27/12/125007
|View full text |Cite
|
Sign up to set email alerts
|

Area spectra of the rotating BTZ black hole from quasinormal modes

Abstract: Following Bekenstein's suggestion that the horizon area of a black hole should be quantized, the discrete spectrum of the horizon area has been investigated in various ways. By considering the quasinormal mode of a black hole, we obtain the transition frequency of the black hole, analogous to the case of a hydrogen atom, in the semiclassical limit. According to Bohr's correspondence principle, this transition frequency at large quantum number is equal to classical oscillation frequency. For the corresponding c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
79
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 45 publications
16
79
0
Order By: Relevance
“…Introducing a covariant form for the adiabatic invariant, Jiang and Han have combined the oscillating velocity of the black hole horizon to revisit the black hole spectroscopy of the Schwarzschild black hole in the tunneling picture [1]. It has been shown that the area spectrum of the Schwarzschild black hole is described with an equally spacing A = 8π 2 p , which is in agreement with Bekenstein's original proposal [7] and is fully in consistence with the previous findings by combining the black hole property of adiabaticity and the black hole quasinormal frequencies [24][25][26][27][28][29][30][31][32][33][34][35][49][50][51][52].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Introducing a covariant form for the adiabatic invariant, Jiang and Han have combined the oscillating velocity of the black hole horizon to revisit the black hole spectroscopy of the Schwarzschild black hole in the tunneling picture [1]. It has been shown that the area spectrum of the Schwarzschild black hole is described with an equally spacing A = 8π 2 p , which is in agreement with Bekenstein's original proposal [7] and is fully in consistence with the previous findings by combining the black hole property of adiabaticity and the black hole quasinormal frequencies [24][25][26][27][28][29][30][31][32][33][34][35][49][50][51][52].…”
Section: Introductionsupporting
confidence: 68%
“…Following this new explanation and the black hole property of adiabaticity, it has been shown that the equally spaced area spectrum of a slowly rotating black hole can be expressed as the form A = 8π 2 p [25], which is exactly equal to the original result of Beken-stein [7]. Later, much further work has shown that the black hole spectroscopy in more general gravity frames can also be properly reproduced by combining the new explanation for quasinormal mode frequency and the black hole property of adiabaticity [24][25][26][27][28][29][30][31][32][33][34][35][49][50][51][52].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Later, by considering the asymptotic QNMs of a black hole, it was proposed that the transition frequency in quantum levels of black holes is relevant to the imaginary part of the QNMs in the semi-classical limit [47]. By identifying an action variable in a black hole system with this transition frequency, it was proposed that the following quantization condition is obtained via the Bohr-Sommerfeld quantization in the semi-classical limit [48]:…”
Section: Entropy Spectrum From the Asymptotic Quasinormal Modesmentioning
confidence: 99%
“…In particular, it was found in lots of literatures [29,48,49,50,51,52,53,54,55,56] that the entropies of black holes in diverse gravity theories are quantized with same spacing. Our results are also consistent with the universal property of equidistant entropy spectrum.…”
Section: Entropy Spectrum From the Asymptotic Quasinormal Modesmentioning
confidence: 99%